The Effect of Health Center Service and Role of Husband Towars Contraceptive Use in Makassar City, Indonesia - Dewi Rahmawati; Apik Indarty Moedjiono; Sukri Palutturi (Health Notions, 2019)
Contraceptive use is one way to reduce population growth rates. This research is aim to measure the effect of health center service and husband role on contraception use in makassar city. This research is done at the Tamalanrea Health Center and Kassi-Kassi Health Center, Makassar Regency. The research design used was a cross sectional study. Research the sample was 178 people who were selected using the startified random sampling technique. Data analyzed using the chi-square test and logistic regression. The result shows that public health center services that are related to use of contraception in makassar city are the choice of contraception (p-value = 0.001), information provided (p-value = 0,000), officer technical ability (p-value = 0,000) and husband-communication wife p-value = 0.007). Information provided is the most influential variable on contraceptive use in the city of makassar with a wald value (42,958) Keywords: contraception; family planning; health center services; husband’s role